AKTIVITAS ANTIOKSIDAN DAN SITOTOKSIK EKSTRAK ETANOL DAUN KARAS TULANG (Chloranthus erectus) TERHADAP SEL HELA - Prastanti, Rovina Friska; Haryoto (Jurnal Insan Farmasi Indonesia, 2024)
Karas tulang (Chloranthus erectus) is a type of herbal plant commonly  found in tropical climates, including Indonesia. Previous research has shown that plants from the Chloranthus genus contain chemical compounds such as flavonoids, which have potential as antioxidants and anticancer agents. This research aims to determine the compound content, test the radical inhibitory activity, and evaluate the cytotoxic activity of karas tulang (Chloranthus erectus) leaves. Antioxidant activity was tested using the DPPH method, with vitamin C as a comparison, while cytotoxicity testing was conducted using the MTT method, with doxorubicin as a positive control. Additionally, a phytochemical screening test was permormed to identify the groups of chemical compounds present in the ethanol extract of karas tulang leaves. The results of the research show that the ethanol extract of karas tulang leaves has very strong antioxidant activity, indicated by an IC50 value of 36.74 μg/mL. Meanwhile, the IC50 value for the cytotoxic test is 163 μg/mL, which falls within the moderate activity category. Based on these test results, it can be concluded that the ethanol extract of karas tulang leaves has the potential to be developed as a safe chemopreventive agent